Cognitive Adaptation Training Provided to Chronically Hospitalized Patients with Schizophrenia in The Netherlands: Two Case Reports - Quee, Piotr J.; Schneider, Harald; van Slogteren, Saskia; Wiersma, Durk; Bruggeman, Richard; Velligan, Dawn I. (Case Reports in Psychiatry, 2012)
Cognitive adaptation training (CAT) improves functional outcome in outpatients with schizophrenia living in the United States of America. The efficacy of CAT has never been demonstrated for patients living in a residential facility. We describe how CAT was delivered to two chronically hospitalized patients with schizophrenia living in The Netherlands. CAT was delivered for 8 months, and consisted of weekly home visits by a psychiatric nurse. Both patients improved on measures of functional outcome used in the US studies. These results indicate that CAT may improve outcomes, even in patients that have been hospitalized for several years.